2015
DOI: 10.1038/bjc.2015.62
|View full text |Cite
|
Sign up to set email alerts
|

The South West Area Mesothelioma and Pemetrexed trial: a multicentre prospective observational study evaluating novel markers of chemotherapy response and prognostication

Abstract: Background:Robust markers that predict prognosis and detect early treatment response in malignant pleural mesothelioma (MPM) would enhance patient care.Methods:Consecutive patients with MPM who were considered fit for first-line chemotherapy were prospectively recruited. Patients of similar performance status opting for best supportive care were included as a comparator group. Baseline and interval CT, PET-CT and serum markers (mesothelin, fibulin-3 and neutrophil–lymphocyte ratio (NLR)) were obtained, and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 27 publications
4
66
1
Order By: Relevance
“…A falling SMRP level at completion of chemotherapy is strongly associated with a longer survival 75 . Baseline SMRP was unable to predict survival.…”
Section: Section 7: Use Of Biomarkersmentioning
confidence: 89%
“…A falling SMRP level at completion of chemotherapy is strongly associated with a longer survival 75 . Baseline SMRP was unable to predict survival.…”
Section: Section 7: Use Of Biomarkersmentioning
confidence: 89%
“…Systemic inflammation in patients with malignancy is considered to reflect the cytokine profile produced both by the tumour and as a component of the host response to the tumour [34]. Increased levels of systemic inflammation have been shown to correlate with worse survival and a poor response to treatment in a number of solid organ tumours [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…We used a more stringent cutoff value of a −50% change in MPF to define the biomarker response compared with the previous reports 1721 ; this cutoff was supported by our correlative analysis of CT and MPF responses in patients with MM. Such a stringent cutoff correlates with the mRECIST criterion of a 30% reduction in the sum for all target lesions and thus leads to a significant reduction of false-positive reports during monitoring.…”
Section: Discussionmentioning
confidence: 90%
“…15,16 Previous studies showed correlations between the computed tomography (CT) response and arbitrarily chosen 10% to 25% reduced serum mesothelin after chemotherapy. 1721 Such low cutoff values are incompatible with a 30% reduction in tumor determined with CT, would contribute to high degrees of false signals, and would make it more difficult to correlate with clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%